Olfactory Information Storage Engages Subcortical and Cortical Brain Regions That Support Valence Determination. (11th August 2021) - Strauch, Christina; Hoang, Thu-Huong; Angenstein, Frank; Manahan-Vaughan, Denise
Abstract: The olfactory bulb (OB) delivers sensory information to the piriform cortex (PC) and other components of the olfactory system. OB-PC synapses have been reported to express short-lasting forms of synaptic plasticity, whereas long-term potentiation (LTP) of the anterior PC (aPC) occurs predominantly by activating inputs from the prefrontal cortex. This suggests that brain regions outside the olfactory system may contribute to olfactory information processing and storage. Here, we compared functional magnetic resonance imaging BOLD responses triggered during 20 or 100 Hz stimulation of the OB. We detected BOLD signal increases in the anterior olfactory nucleus (AON), PC and entorhinal cortex, nucleus accumbens, dorsal striatum, ventral diagonal band of Broca, prelimbic–infralimbic cortex (PrL-IL), dorsal medial prefrontal cortex, and basolateral amygdala. Significantly stronger BOLD responses occurred in the PrL-IL, PC, and AON during 100 Hz compared with 20 Hz OB stimulation. LTP in the aPC was concomitantly induced by 100 Hz stimulation. Furthermore, 100 Hz stimulation triggered significant nuclear immediate early gene expression in aPC, AON, and PrL-IL. The involvement of the PrL-IL in this process is consistent with its putative involvement in modulating behavioral responses to odor experience. Furthermore, these results indicate that OB-mediated information storage by the aPC is embedded in a connectome that supports valence evaluation.